Parents’ Perspectives and Decisions toward Homeschooling for Early Childhood (A Study at Charlotte Mason Indonesia Community) (Journal of Primary Education, 2020)
The objective of the research is investigating parents’ perspectives and decisions toward homeschooling at Charlotte Mason Indonesia Community (KCMI). The subject of the research is three parents who have children aged 4-6 years joining at KCMI. Qualitative phenomenology is selected as the research method. The data collecting techniques are interview, observation, and documentation. The data analyzing technique employ Miles and Huberman’s concept, namely data reduction, data presentation, and conclusions. The results reveal that: The reason of parents in choosing homeschooling varies. First, the difference between the concept of ideal education in the family and the system of educational institutions in Indonesia. Second, the dissatisfaction with the practice of early childhood education in the formal institution. Third, stimulating from reading books and articles on the internet about proper children's education, then reflecting it on education in Indonesia. Three parents choose KCMI as a place to develop and apply Charlotte Mason’s thoughts or philosophy about ideal child and education which is in line with the family principles.